The Human Resource Management of Political Staffers Insights from Prime Ministers' Advisers and Reformers - Lees-Marshment, Jennifer (Taylor & Francis, 2024)
Best practice, HRM, Human resources, Mental health, Political staffer, Prime Minister, Prime Minister's Office, SpAd, Special Adviser, Chief of staff, Government, Human Resource Management, Morale, Office structure, Orientation, Performance management, Political adviser, public administation, training, well-being, work-life balance, workload